Lipoprotein Associated Phospholipase A2 Activity and Itâs Additive Value inCardiovascular Risk Stratification - W, Andi; C, Miryanti; R, Saifur; H, Dadang; ., Widodo (UNEJ e-Proceeding, 2014)
Background: Lipoprotein associated phospholipase A2Â (Lp-PLA2) has been known as a usefulÂ inflammatory marker of cardiovascularÂ risk. FraminghamÂ scoreÂ hasÂ alsoÂ been widelyÂ usedÂ inÂ longÂ termÂ cardiovascularÂ riskÂ stratification.Â However,Â itÂ remainÂ toÂ be clarified whether increased Lp-PLA2 activity and Framingham score significantly increase odd ratio (OR) in acute myocardial infarction (AMI) setting. We therefore investigated Lp- PLA2 activityÂ andÂ itâsÂ additiveÂ valueÂ forÂ FraminghamÂ cardiovascularÂ riskÂ among myocardial infarction men.Blood samples were drawn from 60 men admitted to intensive care unit early after myocardial infarction and 40 healthy men with negative treadmill test as a control. Framingham score were calculated among all subjects. We measured Lp-PLA2 activity by ELISA. Lp-PLA2Â activity was significantly higher in patients with myocardial infarction than those in controlÂ (83.97Â±27.15Â nmol/ml/minuteÂ vs.Â 57.48Â±32.30Â nmol/ml/minute; p=0.000). ROC analysis was performed to identify the most useful Lp-PLA2 cut-off level. Lp-PLA2 activity equal to or more than 74.21Â nmol/ml/minute associated with myocardial infarction with accuracy 68%. The OR of AMI was increased by Lp-PLA2Â activity added to Framingham score from 0.89(CI 95% 0.38- 2.11) to 4.48(CI 95% 1.90- 10.56) Conclusion:Â AdditionÂ ofÂ Lp-PLA2Â Â activityÂ toÂ FraminghamÂ scoreÂ mayÂ hasÂ additive predictive value in cardiovascular risk stratification. Keywords: Lp-PLA2, myocardial infarction, cardiovascular risk stratification